Two FT genes synergistically regulate the reproductive transition of loquat - Yuanyuan Jiang; Yunmei Zhu; Ze Peng; Wenbing Su; Jiangrong Peng; Yuan Yuan; Ling Zhang; Zhike Zhang; Xianghui Yang; Yongshun Gao; Shunquan Lin; Chongjian Ma (Horticultural Plant Journal)
Unlike annual flowering plants that exhibit a single reproductive cycle encompassing vegetative growth, flowering, and senescence within a single year, perennial woody trees undergo a transition between vegetative and reproductive growth every year after a long juvenile phase. Most woody fruit trees bloom when it turns warm in spring, and the fruit ripens in summer or autumn. However, as a member of the Maloideae subfamily, the loquat tree blooms in the cold autumn and winter, and the fruit matures in the spring. To explore the regulatory mechanism of loquat flowering, we characterized two FLOWERING LOCUS T homologous genes in loquat, EjFT1 and EjFT2. qRT-PCR results revealed that EjFT1 and EjFT2 exhibited nearly opposite expression patterns in various tissues. EjFT1 was mainly expressed in young tissues; EjFT2 was mainly expressed in mature leaves, open flowers, and fruits. EjFT2 exhibited an obvious circadian rhythm and was regulated by EjCO. After the trees were exposed to short-day conditions or sprayed with exogenous GA3, the expression of EjFT2 was strongly inhibited, and the loquat tree did not produce floral buds. Furthermore, the yeast two-hybrid, bimolecular fluorescence complementation, and Dual-luciferase assay experiments revealed that both EjFT1 and EjFT2 interacted with EjFD, with the EjFT2-EjFD protein complex enhancing the activity of EjAP1-1 and EjAP1-2 promoters, while EjFT1-EjFD inhibited the activity of the EjAP1-1 promoter. Protein structural analysis of EjFT1 and EjFT2 suggested that differences in amino acid residues at Val123/Leu123, Ser157/Ala157, and Val158/Ala158 may be the reason for their functional differences. Our results showed that EjFT1 and EjFT2 may cooperatively regulate the floral bud differentiation of loquat by competitively binding with EjFD. EjFT2 regulates the onset of loquat floral bud differentiation by responding to photoperiod and gibberellin signals, while EjFT1 is involved in the vegetative growth of loquat. These findings provide important clues for the investigation of the regulatory mechanism of loquat flowering and advance the exploration into the multiple roles of FT homologous genes in regulating the reproductive transformation and vegetative growth of flowering plants.